PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP MANAJEMEN LABA - Andayani, Tutut Dwi; SE., M.Si, M. Yusuf (Majalah Neraca, 2011)
The purpose of this study is to analyze the influence of characteristicsâ board of directors on earnings management. The characteristics are defined as proportion of independent directors and multiple directorships of independent directors. Absolute discretionary accrual is used to measure earnings managementÂ Manufacturing firms listed in Indonesian Stock Exchange 1999-2007 is the object of this study. Based on purposive sampling technique, it gets Â 33 firms. Multiple regression analysis and paired sample Â test are used to test the hypothesis .The result of the hypothesis test indicates that Â proportion of independent directors has significantly negative effect on discretionary accruals. The multiple directorships Â of independent directors has significantly positive effect on discretionary accruals.Â Keywords: earnings management, independent Â directors, multiple directorships